Cohort profile: the ChicagO Multiethnic Prevention and Surveillance Study (COMPASS) - Habibul Ahsan; Farzana Jasmine; Muhammad G Kibriya; Briseis Aschebrook-Kilfoy; Liz Stepniak; Rajan Gopalakrishnan; Andrew Craver; Paul Zakin; Saira Tasmin; Karen E Kim; Kathleen H Goss; Marcy List; et al. (BMJ Open)
Purpose The ChicagO Multiethnic Prevention and Surveillance Study or ‘COMPASS’ is a population-based cohort study with a goal to examine the risk and determinants of cancer and chronic disease. COMPASS aims to address factors causing and/or exacerbating health disparities using a precision health approach by recruiting diverse participants in Chicago, with an emphasis on those historically underrepresented in biomedical research.Participants Nearly 8000 participants have been recruited from 72 of the 77 Chicago community areas. Enrolment entails the completion of a 1-hour long survey, consenting for past and future medical records from all sources, the collection of clinical and physical measurement data and the on-site collection of biological samples including blood, urine and saliva. Indoor air monitoring data and stool samples are being collected from a subset of participants. On collection, all biological samples are processed and aliquoted within 24 hours before long-term storage and subsequent analysis.Findings to date The cohort reported an average age of 53.7 years, while 80.5% identified as African-American, 5.7% as Hispanic and 47.8% as men. Over 50% reported earning less than US$15 000 yearly, 35% were obese and 47.8% were current smokers. Moreover, 38% self-reported having had a diagnosis of hypertension, while 66.4% were measured as hypertensive at enrolment.Future plans We plan to expand recruitment up to 100 000 participants from the Chicago metropolitan area in the next decade using a hybrid community and clinic-based recruitment framework that incorporates data collection through mobile medical units. Follow-up data collection from current cohort members will include serial samples, as well as longitudinal health, lifestyle and behavioural assessment. We will supplement self-reported data with electronic medical records, expand the collection of biometrics and biosamples to facilitate increasing digital epidemiological study designs and link to state and/or national level databases to ascertain outcomes. The results and findings will inform potential opportunities for precision disease prevention and mitigation in Chicago and other urban areas with a diverse population.Registration NA.